Implementing Unplugged Coding Activities in Early Childhood Classrooms - Lee, Joohi; Junoh, Jo (Early childhood education journal, 2019)
Coding is defined as the “process of assigning a code (command/rule)” ( http://Techopedia.com ) that allows a machine or a person to act or move (McLennan, https://www.naeyc.org/resources/pubs/tyc/feb2017/creating-coding-stories-and-games , 2017). Though machines operated by a coding system are common in children’s everyday lives, there has been a lack of resources on how to expose young children to coding in a developmentally appropriate manner. This paper aims to address this gap in the field of early education by providing developmentally appropriate guidelines for teachers of young children to utilize when implementing coding in their classrooms. Specifically, this paper focuses on unplugged coding activities that do not involve computers or computer programming and presents practical examples of tasks with algorithm designs, including a detailed step-by-step instruction set for solving a problem or completing a task (Tynker, https://www.tynker.com/blog/articles/ideas-and-tips/how-to-explain-algorithms-to-kids/ , 2019). This paper presents coding practices that involve children’s daily lives, incorporating sequential and directional commands and coding grids (coding sheet).